Variation of physical durability between LLIN products and net use environments: summary of findings from four African countries - Albert Kilian; Emmanuel Obi; Paul Mansiangi; Ana Paula Abílio; Khamis Ameir Haji; Sean Blaufuss; Bolanle Olapeju; Stella Babalola; Hannah Koenker (Malaria Journal, 2021)
Abstract Background Physical durability of long-lasting-insecticidal nets (LLIN) is an important aspect of the effectiveness of LLIN as a malaria prevention tool, but there is limited data on performance across locations and products. This secondary analysis of data from the VectorWorks project from 10 sites in four African countries involving six LLIN brands provides such data. Methods A total of 4672 campaign nets from 1976 households were recruited into prospective cohort studies 2–6 months after distribution through campaigns and followed for 3 years in Mozambique, Nigeria, DRC and Zanzibar, Tanzania. LLIN products included two 100 denier polyester LLIN (DawaPlus® 2.0, PermaNet® 2.0) distributed in five sites and four 150 denier polyethylene LLIN (Royal Sentry®, MAGNet®, DuraNet©, Olyset™ Net) distributed in five sites. Primary outcome was LLIN survival in serviceable condition and median survival in years. Net use environment and net care variables were collected during four household surveys. Determinants of physical durability were explored by survival analysis and Cox regression models with risk of failure starting with the first hanging of the net. Results Definite outcomes for physical durability were obtained for 75% of study nets. After 31 to 37 months survival in serviceable condition varied between sites by 63 percentage-points, from 17 to 80%. Median survival varied by 3.7 years, from 1.6 to 5.3 years. Similar magnitude of variation was seen for polyethylene and polyester LLIN and for the same brand. Cox regression showed increasing net care attitude in combination with exposure to net related messages to be the strongest explanatory variable of survival. However, differences between countries also remained significant. In contrast, no difference was seen for LLIN material types. Conclusions Variation in net use environment and net care is the main reason for differences in the physical durability of LLIN products in different locations. While some of these factors have been identified to work ...